Relationship of sleep and activity, assessed via a wristwatch-type pulsimeter with an accelerometer, with health status in community-dwelling older adults: A preliminary study. - Akiyo Sasaki-Otomaru; Kyoko Saito; Kotaro Yamasue; Osamu Tochikubo; Yuka Kanoya (PLoS ONE)
Wearable devices have the potential to promote a healthy lifestyle; however, studies on the use of wearable devices in monitoring health in older adults are limited. We aimed to investigate the relationship of sleep and activity data with health status among older adults. Fifty-five community-dwelling older adults were asked to wear a wristwatch-type wearable device (the Pulsense [PS]) and measure home blood pressure (HBP) over a period of 5-7 consecutive days. Deep-sleep duration, physical and mental activity duration, and body-movement duration were obtained from PS data using special software. We also collected data on demographics and physical and mental health status. We found that the body-movement duration in women was longer than that in men. Among men, body-movement duration was strongly and negatively correlated with the Kihon Checklist (KCL) score. It also showed moderate correlations with the Geriatric Depression score, physical functioning, bodily pain, vitality, social function, and role emotional scores from the Medical Outcomes Survey Short Form-8 questionnaire, as well as with hand-grip strength. There was no significant correlation between monitoring data and health status in women. In the multiple linear regression analysis, body-movement duration was negatively associated with age and the KCL score. KCL is a common questionnaire for screening frailty in Japan. Our results showed that body-movement duration was negatively associated with age and the KCL score, suggesting the potential of PS in guiding personalized health management of older community-dwelling adults with risks of frailty.